Regioselective approach to colchiceine tropolone ring functionalization at C(9) and C(10) yielding new anticancer hybrid derivatives containing heterocyclic structural motifs - Krystian Pyta; Natalia Skrzypczak; Piotr Ruszkowski; Franz Bartl; Piotr Przybylski (Taylor & Francis Group, 2022)
The influence of base type, temperature, and solvent on regioselective C(9)/C(10) "click" modifications within the tropolone ring of colchiceine (2) is investigated. New ether derivatives of 2, bearing alkyne, azide, vinyl, or halide aryl groups enable assembly of the alkaloid part with heterocycles or important biomolecules such as saccharides, geldanamycin or AZT into hybrid scaffolds by dipolar cycloaddition (CuAAC) or Heck reaction. Compared to colchicine (1) or colchiceine (2), ether congeners, as e.g. 3e [IC50s(3e) ∼ 0.9 nM], show improved or similar anticancer effects, whereby the bulkiness of the substituents and the substitution pattern of the tropolone proved to be essential. Biological studies reveal that expanding the ether arms by terminal basic heterocycles as quinoline or pyridine, decreases the toxicity in HDF cells at high anticancer potency (IC50s ∼ 1-2 nM). Docking of ether and hybrid derivatives into the colchicine pocket of αGTP/β tubulin dimers reveals a relationship between the favourable binding mode and the attractive anticancer potency.